Tecnologias de informação e comunicação e produtividade na indústria de transformação paulista - Wanderson Luiz Lopes Fortunato (2009)
The diffusion of the information and communication technologies ICT accompanied by decline in the productivity growth rates presented by the U.S. economy starting in the early 1970s raised several questions on the impacts of those technologies over the productivity. This was known as the productivity paradox. Several studies have the purpose of testing the association between the technology and economic performance. These studies raised some explanations about the so called paradox. Some highlight measure errors; others argue that there is a time gap between the diffusion and the internalization of the economic benefits provided by these technologies. In Brazil, this discussion has not gone far. Therefore, this work helps filling this gap. More specifically, we analyze the absorption these technologies by the Brazilian industrial sector. In addition to some discussion about the context in which the technology is disseminated, this work presents an empirical analysis of the role played by the computers, networks and some of their applications in the industrial structure. Also, we verify of association between the degree use of ICT and level of the firms productivity. The database used in this work comprises the transformation industry of the Sao Paulo state in 1996 and 2001. The results show that the diffusion of technology over this industrial sector has evolved significantly in that period. However, in most cases there is still a long way to go, even though in 2001 the indicators show a high level of technological diffusion. Finally, this work identifies a positive relationship between the absorption of ICT and the firms productivity.